Drebrin Isoforms Critically Regulate NMDAR- and mGluR-Dependent LTD Induction - Yasuda, Hiroki; Kojima, Nobuhiko; Hanamura, Kenji; Yamazaki, Hiroyuki; Sakimura, Kenji; Shirao, Tomoaki (Frontiers in Cellular Neuroscience, 2018)
Drebrin is an actin-binding protein that is preferentially expressed in the brain. It is highly localized in dendritic spines and regulates spine shapes. The embryonic-type (drebrin E) is expressed in the embryonic and early postnatal brain and is replaced by the adult-type (drebrin A) during development. In parallel, NMDAR-dependent long-term depression (LTD) of synaptic transmission, induced by low-frequency stimulation (LFS), is dominant in the immature brain and decreases during development. Here, we report that drebrin regulates NMDAR-dependent and group 1 metabotropic glutamate receptor (mGluR)-dependent LTD induction in the hippocampus. While LFS induced NMDAR-dependent LTD in the developing hippocampus in wild-type mice, it did not induce LTD in developing drebrin E and A double knockout (DXKO) mice, indicating that drebrin is required for NMDAR-dependent LTD. On the other hand, LFS induced robust LTD dependent on mGluR5, one of group 1 mGluRs, in both developing and adult brains of drebrin A knockout (DAKO) mice, in which drebrin E is expressed throughout development and adulthood. Agonist-induced mGluR-dependent LTD was normal in wild-type and DXKO mice; however, it was enhanced in DAKO mice. Also, mGluR1, another group 1 mGluR, was involved in agonist-induced mGluR-dependent LTD in DAKO mice. These data suggest that abnormal drebrin E expression in adults promotes group 1 mGluR-dependent LTD induction. Therefore, while drebrin expression is critical for NMDAR-dependent LTD induction, developmental conversion from drebrin E to drebrin A prevents robust group 1 mGluR-dependent LTD.